Hadith #3389 - Sunan Abi Dawud - Abdur Rahman bin Ishaq عبد الرحمن بن إسحاق بن عبد الله; Abu 'Ubaida bin Muhammad bin Yasir أبو عبيدة بن محمد بن عمار بن ياسر العنسي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Walid bin Abi al-Walid الوليد بن أبي الوليد عثمان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
I heard Ibn Umar say: We did not see any harm in sharecropping till I heard Rafi’ ibn Khadij say: The Messenger of Allah (ﷺ) has forbidden it. So I mentioned it to Tawus. He said: Ibn Abbas told me that the Messenger of Allah (ﷺ) had not forbidden it, but said: It is better for one of you to lend to his brother than to take a prescribed sum from him.
Grade: Sahih